Nonlinear buckling and critical current degradation of superconducting wires with complex cross sections - Feng Xue; Kexin Zhou; Xiaofan Gou (AIP Advances)
Bi2Sr2CaCu2Ox (Bi2212) is a superconducting material with a high critical superconducting temperature, making it advantageous for manufacturing high-temperature superconducting round wires. However, Bi2212 is a ceramic-like material with poor toughness, making it prone to fracture under mechanical loads, which, in turn, reduces the critical current of the wires. In this paper, we conducted a numerical study on the current degradation of Bi2212 superconducting round wires under compressive strain based on the finite element method (FEM). We proposed a coupling FEM model with a combination of a 1D beam model and a 3D solid model. Due to the irregularity of the Bi2212/Ag interface, we adopted a pure Bi2212/Ag interface cross section. Pre-stress was applied to induce buckling deformation in the super-conducting wire, followed by the application of compressive strain, which caused fracture in the Bi2212 filaments. This fracture was induced by the buckling deformation of the superconducting wire. By analyzing the current flow through the damaged superconducting wire, we obtained a relationship curve between compressive strain and critical current. The results indicate that the critical current degradation of Bi2212 superconducting round wires under compressive strain is primarily due to tensile failure of the Bi2212 filaments.